SoTL as Reconciliation: Seeking to contribute to decolonization and Indigenization of teaching, learning, and research in Canadian Universities - Hill, Joshua (Imagining SoTL)

(untitled) (Mount Royal University Library in partnership with University of Alberta Library, 2024)
In this article, I develop guiding questions to explore ways that the Scholarship of Teaching and Learning (SoTL) can contribute to advancing reconciliation in Canadian universities. I draw on decolonization and Indigenization literature to reflect on my SoTL practice, identify tensions, and look ahead to next steps in my research. Ultimately, I aim to invite co-reflection and extend dialogue within the community of SoTL scholars towards contributing to reconciliation through SoTL.